2008
DOI: 10.1099/mic.0.2008/018440-0
|View full text |Cite
|
Sign up to set email alerts
|

The Yersinia pseudotuberculosis and Yersinia pestis toxin complex is active against cultured mammalian cells

Abstract: The toxin complex (Tc) genes were first identified in the insect pathogen Photorhabdus luminescens and encode~1 MDa protein complexes which are toxic to insect pests. Subsequent genome sequencing projects have revealed the presence of tc orthologues in a range of bacterial pathogens known to be associated with insects. Interestingly, members of the mammalianpathogenic yersiniae have also been shown to encode Tc orthologues. Studies in Yersinia enterocolitica have shown that divergent tc loci either encode inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
64
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 44 publications
3
64
2
Order By: Relevance
“…Our results indicate that although the Y. pestis Tc proteins are not insecticidal, they are active against PMNs. This is in agreement with previous studies which have shown that Y. pestis and Yersinia pseudotuberculosis Tc proteins are not toxic to Sf9 insect cells, M. sexta larvae, or X. cheopis (12,13) but are active against mammalian NIH 3T3 and Caco-2 cells (12). Additionally, Yersinia enterocolitica Tc protein homologues are only mildly insecticidal and nematocidal when fed orally (33)(34)(35) but are important in colonization of the gastrointestinal tract of mice (36).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our results indicate that although the Y. pestis Tc proteins are not insecticidal, they are active against PMNs. This is in agreement with previous studies which have shown that Y. pestis and Yersinia pseudotuberculosis Tc proteins are not toxic to Sf9 insect cells, M. sexta larvae, or X. cheopis (12,13) but are active against mammalian NIH 3T3 and Caco-2 cells (12). Additionally, Yersinia enterocolitica Tc protein homologues are only mildly insecticidal and nematocidal when fed orally (33)(34)(35) but are important in colonization of the gastrointestinal tract of mice (36).…”
Section: Discussionsupporting
confidence: 81%
“…Tc proteins of Y. pestis (9), Y. pseudotuberculosis (12,39), P. luminescens (1,40), Y. entomophaga (37), and X. nematophilus (41) have been shown to form large-molecular-weight protein complexes. In general, Tc protein complexes are composed of class A (TcA; Y. pestis YitA and YitB), class B (TcB; Y. pestis YitC), and class C (TcC; Y. pestis YipA and YipB) Tc proteins (9,37,(41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Class B proteins are ϳ170 kDa, and class C proteins are ϳ110 kDa. There are many different varieties of class A, B, and C proteins in both Gram-negative and Gram-positive bacteria (12)(13)(14)(15).…”
mentioning
confidence: 99%